(untitled) (Research, Society and Development, 2021)
The Amazon region has a great diversity of plants rich in bioactive compounds, whose rational exploitation contributes to the sustainable development of the region. Among these stand out andiroba (Carapa guianeses) and açaí (Euterpe oleracea), from which oils are extracted that have great potential to be used in the cosmetic, pharmaceutical, food and even in the production of renewable fuel. Thus, the objective was to carry out bibliographic research on the methods of extraction of andiroba and açai oils, as well as their applications in the industry and new technological innovations. Such oils are widely used in popular medicine due to their numerous medicinal properties. Andiroba oil has anti-inflammatory, antimicrobial, insecticide, etc., which are mainly attributed to its limonoid content. Açaí oil, on the other hand, has a large amount of phenolic compounds, such as anthocyanins and a profile of fatty acids that are beneficial to health, being widely used as an antioxidant, anticarcinogenic agent, fighting cardiovascular and neurodegenerative diseases. There are numerous methods used to extract these oils, including artisanal, cold pressing, supercritical fluid, organic solvents, enzymatic, etc. Even so, the cold pressing method is still the most used by industries, since it obtains better quality products and preserves their bioactive compounds, and the cosmetics market is the one that most uses these oils.